Real-world data in late presentation of HIV infection in Suzhou, China: Results from four consecutive cross-sectional surveys, 2017-2020 - Zhihui Xu; Qiang Shen; Di Wang; Zefeng Dong; Weining Han; Runfang Tian; Kai Zhou; Xuerong Ya; Haiyang Hu (Frontiers Media S.A., 2023)
ObjectivesThis study aimed to examine the real prevalence of late presentation of HIV infection and to identify factors associated with late HIV presentation among patients with newly diagnosed HIV/AIDS in Suzhou, China.MethodsPatients with newly diagnosed HIV/AIDS who registered in national AIDS surveillance system from 2017 to 2020 were included in this study. Late presentation (LP) of HIV infection was defined as HIV diagnosis with a CD4 count < 350 cells/μL or an AIDS-defining event. Multivariable logistic regression analyses were used to identify factors associated with LP.ResultsA total of 2,300 patients were enrolled. 1,325 were classified as late presenters, showing a high percentage of 57.6% (95% CI: 54.5-60.7%) and a rise (P = 0.004) over the four-year period. Patients with newly diagnosed HIV/AIDS who were older than 24 years of age (aOR = 1.549, P = 0.001 for 25-39 years; aOR = 2.389, P < 0.001 for 40 years and older), were Suzhou registered residents (aOR = 1.259, P = 0.026), and were from inpatient and outpatient (aOR = 1.935, P < 0.001) were more likely to be late presentation.ConclusionsThis study showed a high percentage and a rise of late presentation of HIV infection among patients with newly diagnosed HIV/AIDS in Suzhou, China, which is a challenge for future prevention and control of AIDS. Targeted measures should be urgently implemented to reduce late HIV diagnosis.